Threshold for Radon-Induced Lung Cancer From Inhaled Plutonium Data. Issue 4 (2nd November 2015) - Cuttler, Jerry M.; Sanders, Charles L.
Cohen's lung cancer mortality data, from his test of the LNT theory, do not extend to the no observed adverse effects level (NOAEL) above which inhaled radon decay products begin to induce excess lung cancer mortality. Since there is concern about the level of radon in homes, it is important to set the radon limit near the NOAEL to avoid the risk of losing a health benefit. Assuming that dogs model humans, data from a study on inhaled plutonium dioxide particulates in dogs were assessed, and the NOAEL for radon-induced lung tumors was estimated to be about 2100 Bq/m 3 . The US Environmental Protection Agency should consider raising its radon action level from 150 to at least 1000 Bq/m 3 .